Social determinants of quality of life among PLHIV in Australia: implications for health promotion. (27th February 2021) - Mikołajczak, Gosia; Brown, Graham; Power, Jennifer; Lyons, Anthony; Howard, Chris; Drummond, Fraser
Summary: A cascade of care model is central to contemporary approaches to HIV prevention. The model prioritizes strategies to increase rates of HIV testing and promote early and sustained uptake of antiretroviral treatment (ART) among people living with HIV (PLHIV). The model aims to prevent new HIV transmissions by increasing the number of PLHIV who have achieved HIV viral suppression. However, good quality of life (QoL) among PLHIV has been proposed as an additional goal. This prioritizes the basic right of PLHIV to lead meaningful lives and acknowledges the relationship between better QoL and consistent ART use. A better understanding of factors associated with the QoL can thus inform health promotion programmes for PLHIV. In this study, N =465 Australian participants, recruited through social media and various HIV community organizations, completed an online survey that included a measure of QoL and a range of demographic, health-related and social variables. Overall, social factors accounted uniquely for the most variance in QoL (18%), followed by health-related (11%) and demographic factors (2%). Social support, HIV-related discrimination and treatment convenience were among the strongest determinants of QoL. These findings reinforce the importance of a more holistic approach to health promotion among PLHIV. Specifically, our results indicate that to improve the QoL of PLHIV and to boost related public health benefits, community advocates and healthcare professionals must be responsive to the broader psychological, social and functional needs of PLHIV.